The Role of Google Workspace in Facilitating Collaborative and Participatory Learning Higher Education - Emilzoli, Mario; Hernawan, Asep Herry; Rullyana, Gema; Priandani, Ai Pemi (Journal of Education Technology, 2025)
Digital era of education at all levels is required to adapt and utilize technology to improve the quality of learning. This study investigates the role of Google Workspace in facilitating collaborative and participatory learning among higher education students. The research is driven by the need to address challenges in traditional learning environments, which often lack opportunities for collaboration and active participation. Using a quantitative approach, data were collected from 88 students in Educational Technology program through a survey based on the Technology Acceptance Model (TAM). The study analyzed four key dimensions: Perceived Ease of Use, Perceived Usefulness, Attitude Toward Using, and Behavioral Intention to Use. Results indicated that Google Workspace significantly enhances student collaboration and productivity, with high scores across all dimensions. The findings highlight the platform's potential to improve digital learning strategies and equip students with essential 21st-century skills. Future research should explore the long-term impact of Google Workspace on diverse educational settings and address potential implementation challenges.